The Nuclear Tipping Point : Why States Reconsider Their Nuclear Choices - Editors : Campbell, Kurt M.; Einhorn, Robert J. and Reiss, Mitchell B.; Foreword By Gregorian Vatan (New Delhi Manas Publications, 2005)
The Nuclear Tipping Point provides a framework for understanding the myriad factors that shape nuclear policy. Case studies of eight long-term stalwarts of the nonproliferation regime-Egypt, Germany, Japan, Saudi Arabia, South Koria, Syria, Taiwan, and Turkey-flesh out this framework and show how even these countries might be pushed over the edge of a nuclear tipping point.
Include Index.
Keywords: Nuclear Nonproliferation -- National Security